2006
DOI: 10.1007/bf02854899
|View full text |Cite
|
Sign up to set email alerts
|

Lipid mediator informatics-lipidomics: Novel pathways in mapping resolution

Abstract: A BSTRACTLipidomics, the systematic decoding of lipid-based information in biosystems, is composed of identifying and profi ling lipids and lipid-derived mediators. As currently practiced, lipidomics can be subdivided into architecture/ membrane lipidomics and mediator lipidomics. The mapping of structural components and their relation to cell activation as well as generation of potent lipid mediators and networks involves a mass spectrometry -computational approach so that interrelationships and complex media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 32 publications
0
10
0
1
Order By: Relevance
“…They were initially identified and elucidated using LC-MS-MS-based lipidomics 8,9 and informatics 114 together with bioassay systems. The term resolvins (resolution-phase interaction products) refers to endogenous chemical mediators that are biosynthesized from the major -3 fatty acids, EPA and DHA, denoted E series (RvE) and D series (RvD) resolvins, respectively.…”
Section: Resolvins and Protectinsmentioning
confidence: 99%
“…They were initially identified and elucidated using LC-MS-MS-based lipidomics 8,9 and informatics 114 together with bioassay systems. The term resolvins (resolution-phase interaction products) refers to endogenous chemical mediators that are biosynthesized from the major -3 fatty acids, EPA and DHA, denoted E series (RvE) and D series (RvD) resolvins, respectively.…”
Section: Resolvins and Protectinsmentioning
confidence: 99%
“…The mouse dorsal air pouch is an experimental model of a dermal wound that provides a creative system for investigation of cellular and biochemical effectors of resolution during a self-limited acute inflammatory response. Inflammatory exudates were extracted and subjected to LC-UV-MS-MS-based lipidomic analyses by Serhan and colleagues, leading to the identification of E- and D-series resolvins (reviewed in [89]). Detailed matching studies for pro-resolving actions were performed to confirm the structure-activity relationships for each endogenous compound.…”
Section: Resolvins: ω-3 Pufa-derived Pro-resolving Mediatorsmentioning
confidence: 99%
“…4 In animal models, n-3 FA-rich diets markedly decrease arterial low-density lipoprotein cholesterol deposition 5 in contrast to saturated fat-rich diets, which increase arterial wall cholesterol. 6 In addition to producing potent anti-inflammatory docosanoid catabolites, 7,8 n-3 FA may also be direct ligands for transcription factors 9 and/or may interact with specific receptors important in inflammatory cascades and insulin resistance, 10 pathways important in coronary heart disease. Of note, arachidonic acid also leads to synthesis of potent anti-inflammatory and proresolution lipoxins.…”
Section: See Accompanying Article On Page 2487mentioning
confidence: 99%
“…Of note, arachidonic acid also leads to synthesis of potent anti-inflammatory and proresolution lipoxins. 7 Not all intervention studies have shown the cardiovascular benefit of increased intakes of n-3 FA. This may relate, in part, to initial high baseline intakes in tissue levels of n-3 FA in certain populations (eg, Japanese individuals); short duration of interventions; small cohort sizes; a comparison of n-3 FA intervention studies using increasing intakes of ␣-linolenic acid (the essential FA precursor for EPA and DHA) with studies in which EPA and DHA are administered themselves; and studies that do not consider the baseline intakes of n-6 FA.…”
Section: See Accompanying Article On Page 2487mentioning
confidence: 99%